Polyvinyl alcohol/silica hybrid microspheres: synthesis, characterization and potential applications as adsorbents. (1st February 2019) - Teng, Shu-Hua; Niu, Niu; Chen, Feng-Wu; Wang, Peng
Abstract: Polyvinyl alcohol/silica (PVA/SiO2 ) hybrid microspheres with different SiO2 contents were prepared via a sol-gel combined emulsification process. When 20 wt% SiO2 was contained, the hybrid microspheres (∼13.3 μ m in average diameter) presented the most desirable morphology with good spherical shape, high dispersity and uniform particle size. Silica xerogel existed as an amorphous phase in the microspheres, and its actual content was determined by the TG analysis. The feasibility of the hybrid microspheres as a novel adsorbent to remove Rhodamine B (RhB) was preliminary evaluated in aqueous solutions. A kinetic study indicated that the adsorption data were well represented by the pseudo-second-order model. Moreover, the removal efficiency of RhB by the hybrid microspheres was found to depend strongly on the SiO2 content. Under the optimal adsorption conditions, the hybrid microspheres with 20 wt% SiO2 exhibited the highest removal percentage of RhB (∼88.4%), indicating their great potential to be used in water treatment applications.